Aus-einander-setzung zwischen Hermeneutik und Dekonstruktion und Gadamers Solidaritätsverständnis - Shiratori, Maya (Labyrinth, 2022)
Aus-einander-setzung between Hermeneutics and Deconstruction and Gadamer's Concept of Solidarity This paper will analyze the debate between Gadamer and Derrida and Gadamer's concept of solidarity. The previous research literature focused only on their first debate, which could only lead to limited results, even though the exchange between these two philosophers continued after the first debate. In addition, Gadamer revised a large part of his speech, which caused the first debate with Derrida, for publication. In this way, the accentuation of concepts and themes that Derrida found problematic in the published version differs considerably from that in Gadamer's real speech. For this reason, this paper will consider Gadamer's original manuscript, which is preserved in Deutsches Literatur Archiv in Marbach. My point is that in Derrida's funeral oration for Gadamer, Uninterrupted Dialogue, can be found some shared points of view between both philosophers, namely their interpretation of Paul Celan's poems. By means of their Celan interpretations, I will demonstrate that it is not good will that unites all human beings, but their existential fate to find death. Here we encounter the problem of solidarity in Gadamer's work, since in his interpretation of Celan he considers death (or mortality) to be the "ultimate solidarity" of human beings, whereas in his other texts he defines solidarity as a kind of friendship. Hence, Gadamer's understanding of solidarity is discussed in the last part of this paper. My argument is that the concept of solidarity and that of belonging are interconnected in Gadamer's texts and that in this point the concept of openness shows its fundamental role.